Primary health care centres in Madagascar - Andrianarisoa, A O; Rampanjato, M (World health forum, 1994)
In 1976, Madagascar promised to establish 1500 primary health care centers to be run by a community health agent. The communities selected sites for the centers, nominated health agent candidates, built and maintained the centers and accommodation for the health agents, supplied the centers, and undertook their operation. The government organized the recruitment and training of the agents, paid their wages, and provided equipment and drugs. The candidates were 18-28 years old and had completed two years of secondary education. Training lasted 14 months and enabled the new agents to provide basic health care in the curative, preventive, and educational fields. The health agents can deal with normal births, family planning, vaccination, and health education. In 1991 the country had 1935 facilities that were providing primary care. Some 85% of the health agents have remained in the primary health care centers for over 10 years; 50 agents have moved out to become nurses or midwives. Financial support for the program comes from the state and external donors. Of the 1500 planned primary health care centers, 461 stopped functioning, mostly because the communities concerned have not adequately built and maintained premises for the health agents. The primary health care centers are less frequently attended than formerly because equipment is aging and drugs are in short supply. Cost recovery should be widely adopted in the national health system. More in-service training should be provided for health agents, and more tours of inspection should be carried out. Community health workers should be managed entirely by the community, and the Ministry of Health should take charge of their training. Primary health care in Madagascar has largely proved its worth; if the economic handicaps can be overcome, the program is likely to contribute to the achievement of the health-for-all goals.